Diagnosis of Vascular Rupture Due to Arteriovenous Malformation Using Postmortem Angiography and 3-Dimensonal Printing: A Case Report. (September 2021) - Mi, Jingya; Dong, Hewen; Wan, Lei; Zou, Donghua; Li, Zhengdong; Tian, Zhiling; Wang, Zhuoqun; Liu, Ningguo; Chen, Yijiu
Abstract : Abstract: Postmortem computed tomography (PMCT), PMCT angiography, and 3-dimensonal (3D) printing technology are increasingly applied to forensic practice. Although their effectiveness is undeniably confirmed, their potential role in practice still needs to be further explored. Here, we report a typical case in which such 4 technologies were applied to a woman found dead with stomach content beneath the head on the pillow in her residence. At first, the cause of death was simply considered as hypertensive cerebral hemorrhage after preliminary examination. However, the initial judgment was questioned by her family for her devoid of hypertension history. As indicated by the targeted PMCT with cerebral angiography, the woman died of pathological cerebral hemorrhage due to arteriovenous malformation, which was still unconvincing enough for the family because in violent death, some cerebral hemorrhage could also be located in the same position. Finally, the family came to be convinced when the close connection between the deformed blood vessels and hematoma was perfectly demonstrated by the application of 3D printing technology. This study proved that it can be an efficient tool for identifying the cause of death when the integration is made of 3D printing technology and PMCT angiography, as a more intuitive evidence of forensic science.